2019
DOI: 10.1016/s1473-3099(18)30792-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbapenem resistance on outcomes of bloodstream infection caused by Enterobacteriaceae in low-income and middle-income countries (PANORAMA): a multinational prospective cohort study

Abstract: 2019. Effect of carbapenem resistance on outcomes of bloodstream infection caused by Enterobacteriaceae in lowincome and middle-income countries (PANORAMA): a multinational prospective cohort study. Lancet Infectious Diseases 19 (6) , pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 45 publications
(45 reference statements)
4
101
1
4
Order By: Relevance
“…26 Recently, a multinational prospective cohort study was performed that evaluated the effect of carbapenem resistance on outcomes of bloodstream infections due to Enterobacteriaceae in low-and middle-income countries. 27 This study reports a crude mortality rate of 35% (43/123 patients) for patients with carbapenem-resistant Enterobacteriaceae (CRE) bloodstream infections, similar to other reported rates ranging from 26 to 44%. 28 In addition, the authors found that CRE bloodstream infection was associated with an increased length of hospital stay (3.7 days, 95% CI: 0.3-6.9) and increased probability of in-hospital mortality (hazard ratio: 1.75; 95% CI: 1.04-2.94) compared with carbapenem-sensitive infections.…”
Section: Antibiotic Resistance In Low-and Middle-income Countriessupporting
confidence: 82%
“…26 Recently, a multinational prospective cohort study was performed that evaluated the effect of carbapenem resistance on outcomes of bloodstream infections due to Enterobacteriaceae in low-and middle-income countries. 27 This study reports a crude mortality rate of 35% (43/123 patients) for patients with carbapenem-resistant Enterobacteriaceae (CRE) bloodstream infections, similar to other reported rates ranging from 26 to 44%. 28 In addition, the authors found that CRE bloodstream infection was associated with an increased length of hospital stay (3.7 days, 95% CI: 0.3-6.9) and increased probability of in-hospital mortality (hazard ratio: 1.75; 95% CI: 1.04-2.94) compared with carbapenem-sensitive infections.…”
Section: Antibiotic Resistance In Low-and Middle-income Countriessupporting
confidence: 82%
“…Increased hospital stay and mortality was shown to be associated with CRE infection in a recent published study. 32 In hospitals that were screened both 2017 and 2018, the increase in CRE prevalence was considerable. This indicates that improvement in IPC measures is urgent, otherwise we may not have seen the peak of this hospital epidemic.…”
Section: Main Findingsmentioning
confidence: 99%
“…However, since their discovery, carbapenemases (e.g., NDM, KPC, and OXA) have emerged as key drivers of carbapenem resistance across various Gram-negative bacterial species [2,3]. Lack of effective treatment and the consequent high mortality [4] has increased emphasis on the prevention of MDRGN transmission. Prevention toolkits and guidelines have been drawn up by various organizations to harness the principles of infection control and prevention to break the chain of transmission and control the spread of MDRGN [5][6][7].…”
Section: Introductionmentioning
confidence: 99%